SISTEM INFORMASI RENTAL KENDARAAN (STUDI KASUS : ANDI RENTAL KENDARAAN) - , SHELLA NURANDIKA PUTRI, Nur Rokhman,S.Si.M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Andi-Vehicle Rental needs an information system which can ease the reservation process. At first, the implemented system in this car rental uses the manual method. Vehicle reservation data and tenant personal data was filled into a paper-based form. This process takes a long time and has possibilities of error due to incomplete data. The same problem occurs to the rental vehicle return, there are many employee that calculated the fine and rental fee inaccurately. This could lead to company loss. Other process such as the processing of vehicle data, driver data, and supplier data also still uses an ineffective process. A proper solution to deal with the problem in Andi-Vehicle Rental is an information system which can handle the process of rental data processing, such as vehicle data, driver data, supplier data, reservation data, and return data. Also, the system has an online vehicle rental reservation, and the return process that can calculate the fine cost based on the delay in vehicle return. Information System of Andi-Vehicle Rental is developed using Laravel software framework, PHP Programming language, and MySQL database. This information system is expected to handle the processing of vehicle data, driver data, and supplier data, ease the reservation process, return process, and also billing and reporting process. Additionally, this system could give a correct information for the vehicle rental users.